Jual Beli Menggunakan Member Card di Tinjau Dari Etika Bisnis Islam (Studi Kasus Chandra Super Store 22 Kota Metro) - Zakiyatun Nufus (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2022)
The implementation of buying and selling using a member card should be based on mutually beneficial transactions, there is no element of deception, coercion and an attitude of mutual pleasure or consensual from both parties and if these elements are not fulfilled then the sale and purchase is invalid. The research question in this study is how are the benefits of buying and selling using a member card at Chandra Super Store 22 Metro City according to Islamic business ethics. The purpose of this study was to determine the benefits of buying and selling in using member cards in terms of Islamic business ethics at Chandra Super Store 22 Metro City and the benefits of this research is that practically the results of this study are expected to contribute ideas to the wider community about member cards in terms of business ethics. Islam and theoretically that the results of this research are expected to contribute to the thought and development of science, especially Islamic economics. The type and nature of this research is descriptive qualitative research. The data sources used are primary data sources, namely customers who have member cards at Chandra Super Store 22 Metro City and secondary data sources, namely data sources obtained from other sources. The method used in this research is interviews, documentation and observation. The data validity technique is checking the results of data about buying and selling using a member card in terms of Islamic business ethics. The data technique uses qualitative analysis, namely the process of searching and compiling sequentially based on data obtained from interviews, field notes and other materials. Based on interviews and observations, the use of member cards in buying and selling transactions is viewed from Islamic business ethics, some scholars allow transactions using member cards but the goods spent must be useful, there is an element of openness and willingness. Making a member card has an element of ambiguity in it. One of the requirements proposed to make a member card is to pay a nominal amount of 10,000 to become a member card member. In making member cards, prospective members are required to pay a fee of 10,000 per card and which must be renewed within a certain period of time there is an element of uncertainty where the card owner does not know whether there will be profit or loss in using the member card. The application and use of member cards at Chandra Super Store 22 Metro City is permissible or legal and does not conflict with Islamic business ethics because there are no elements that are detrimental to buyers/customers, but on the contrary, consumers feel the benefits obtained from the Chandra Super Store 22 Metro City member card.